اختصاص السلطة التشريعية بمجال الصفقات العمومية في القانون الجزائري - بوبرقيق، عبدالرحيم (جامعة محمد بوضياف المسيلة - كلية الحقوق والعلوم السياسية - مخبر الدراسات والبحوث في القانون والأسرة والتنمية الإدارية, 2020)
هذه الدراسة تبحث مشكلة اختصاص السلطة التشريعية في الجزائر أم لا بتحديد قواعد الصفقات العمومية عن طريق التشريع وتهدف إلى إثبات أنه يجوز لتنظيم هذا المجال، وخلافا لما هو سائد في القانون الجزائري في الوقت الحاضر أي تنظيم الصفقات العمومية عن طريق نصوص تنظيمية، استعمال أسلوب التشريع الأصلي الصادر عن السلطة التشريعية أو التشريع بالأوامر الصادر عن رئيس الجمهورية المنصوص عليهما في الدستور الجزائري؛ لأن مجال الصفقات العمومية لا يخرج كليا عن نطاق التشريع، فهناك نصوص في الدستور الجزائري تفرض تنظيمه من خلال هذا الشكل من النصوص القانونية. In Algeria, the executive authority has historically regulated the subject of public procurements by presidential and executive decrees, lately, for instance, the Presidential Decree no. 15-247 of 16 September 2015 relative to Public Procurements and Public Service’s Delegations; even though the Algerian Constitution as amended in 2016 contains several provisions that may serve as basis for a different legitimate solution regarding the regulation of this type of public contracts. This study will examine whether the legislative authority is competent or not to determine public procurements provisions in Algerian law, in the light of the French law and doctrine. It main goal is to show that the legislative authority may make rules of law in matter of public procurements, in contrast to what is found in Algerian law, because there are multiple constitutional provisions imposing that solution. For this purpose, the author will apply the analytical approach including the method of interpretation in order to link the subject of public procurements to the areas of legislation that are defined by the Algerian Constitution. He will conclude that public procurements fall within the domain of legislation according to articles 140 and 141 of the Algerian Constitution. He will also conclude that the regulation of public procurements on the ground of article 140 and 141 previously mentionned can be achieved either by a Parliament Act or by a legislative ordinance promulgated by the President of the executive authority.
Keywords: الصفقات العمومية -- السلطة التشريعية -- الاختصاصات القضائية -- القانون الجزائري